Chlamydia pneumoniae is present in the dental plaque of periodontitis patients and stimulates an inflammatory response in gingival epithelial cells - Cássio Luiz Coutinho Almeida-da-Silva; Tamer Alpagot; Ye Zhu; Sonho Sierra Lee; Brian P. Roberts; Shu-Chen Hung; Norina Tang; David M. Ojcius (Microbial Cell)
Chlamydia pneumoniae is an airborne, Gram-negative, obligate intracellular bacterium which causes human respiratory infections and has been associated with atherosclerosis. Because individuals with periodontitis are at greater risk for atherosclerosis as well as respiratory infections, we investigated the role of C. pneumoniae in inflammation and periodontal disease. We found that C. pneumoniae was more frequently found in subgingival dental plaque obtained from periodontally diseased sites of the mouth versus healthy sites. The known periodontal pathogens, Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans, were also found in the plaque. In addition, C. pneumoniae could efficiently invade human gingival epithelial cells (GECs) in vitro, causing translocation of NF-κB to the nucleus along with increased secretion of mature IL-1β cytokine. Supernatants collected from C. pneumoniae-infected GECs showed increased activation of caspase-1 protein, which was significantly reduced when nlrp3 gene expression was silenced using shRNA lentiviral vectors. Our results demonstrate that C. pneumoniae was found in higher levels in periodontitis patients compared to control patients. Additionally, C. pneumoniae could infect GECs, leading to inflammation caused by activation of NF-κB and the NLRP3 inflammasome. We propose that the presence of C. pneumoniae in subgingival dental plaque may contribute to periodontal disease and could be used as a potential risk indicator of periodontal disease.